Morphological and molecular evidences for a new species of Datroniella (Polyporales, Basidiomycota) from Brazil - de Lira, Carla Rejane Sousa; Ryvarden, Leif; Gibertoni, Tatiana Baptista (Phytotaxa, 2016)
Datroniella minuta sp. nov. from Northeast Brazil is described on the basis of morphological characteristics and ITS and nLSU sequence data analyses. This species is characterized by tiny and cupulate basidiomata and large cylindrical basidiospores. A key for species of Datroniella, drawings of the micro-characteristics, color photograph of the basidiomata and phylogenetic tree to show the placement of the new species are provided.